Final Assembly of the Southwestern Central Asian Orogenic Belt as Constrained by the Evolution of the South Tianshan Orogen: Links With Gondwana and Pangea. Issue 9 (3rd September 2018) - Wang, Xin‐Shui; Klemd, Reiner; Gao, Jun; Jiang, Tuo; Li, Ji‐Lei; Xue, Sheng‐Chao
Abstract: The South Tianshan Orogen marks the final assembly of the southwestern Central Asian Orogenic Belt (CAOB) and the Karakum–Tarim cratons. Here we present an integrated mineralogical, geochemical, and geochronological study of the Wuwamen ophiolitic mélange in the South Tianshan to better understand the tectonic evolution of the western CAOB and its links to Gondwana and Pangea. Mantle peridotites with mineral compositions similar to those of abyssal peridotites and basalts with N‐MORB geochemical affinities suggest that the Wuwamen ophiolite was formed in a mid‐ocean ridge setting. Arc‐related gabbro and plagiogranite stocks intruding the mantle peridotites yielded zircon U–Pb ages of 441.1 ± 4.2 and 442.8 ± 2.4 Ma, indicating that the Wuwamen ophiolite got emplaced prior to ~440 Ma. Sericite‐quartz schist from the ophiolitic mélange matrix with abundant 481–319 Ma detrital zircon grains is crosscut by a two‐mica granite dike with a zircon U–Pb age of 321.3 ± 1.7 Ma, thereby constraining the formation of the Wuwamen ophiolitic mélange at ~320 Ma. In conjunction with published data, we propose that the South Tianshan Ocean opened in the late Neoproterozoic and promoted the subsequent separation of microcontinents in the western CAOB from the northeast Gondwana margin during Gondwana assembly. Furthermore, the closure of the South Tianshan Ocean led to the final assembly of the southwestern CAOB and the Karakum–Tarim cratons and their incorporation into Pangea at ~320 Ma. Key Points: The Wuwamen ophiolite formed in a mid‐ocean ridge setting and got emplaced prior to ~440 Ma The formation of the Wuwamen ophiolitic mélange suggests that the final closure of the South Tianshan Ocean occurred at ~320 Ma The western Central Asian Orogenic Belt was not accreted to Gondwana prior to collision with Karakum–Tarim as part of Pangea at ~320 Ma